A tandem annulation with a [1, 3]-hydride transfer as the key step leading to isochromans. Issue 77 (14th September 2017) - Wang, Yingwei; Li, Guangxun; Liu, Hongxin; Tang, Zhuo; Cao, Yuan; Zhao, Gang
Abstract : The first [1, 3]-hydride transfer/cyclization process for oxacarbenium isomerization. Abstract : An unprecedented method that enables the direct coupling of an α-C–H bond in alcohols with 2-arylacetaldehydes through a [1, 3]-hydride transfer ([1, 3]-HT) of oxocarbenium ions catalyzed by a Lewis acid has been developed. The redox neutral preparation of the isochroman derivatives proceeds via a tandem condensation/[1, 3]-HT/Friedel–Crafts sequence with moderate to good yields. Deuterium-labeling studies provide mechanistic insights and reveal that the redox functionalization proceeds via a [1, 3]-HT.